Sustainability certification for small scale tourism operators in Pulau Perhentian Kechil Terengganu [electronic resource] - Robiah Suratman, 1968-; Amran Hamzah, supervisor; Fakulti Alam Bina (2013)
Thesis (Ph.D (Town and Regional Planning)) - Universiti Teknologi Malaysia, 2013